Pre-vaccine plasma levels of soluble inflammatory indices negatively predict responses to HAV, HBV, and tetanus vaccines in HCV and HIV infection. Issue 4 (25th January 2018) - Shive, Carey L.; Judge, Chelsey J.; Clagett, Brian; Kalayjian, Robert C.; Osborn, Melissa; Sherman, Kenneth E.; Fichtenbaum, Carl; Gandhi, Rajesh T.; Kang, Minhee; Popkin, Daniel L.; Sieg, Scott F.; Lederman, Michael M.; et al.
Abstract: Background: Chronic hepatitis C virus (HCV) and HIV infections are associated with impaired responses to neo-antigens contained in hepatitis A virus (HAV)/hepatitis B virus (HBV) vaccines, yet responsible mechanisms are unclear. Methods: ACTG 5232 and CFAR0910 were clinical trials where pre-vaccine levels of plasma IP10, IL-6, sCD163 and sCD14 were measured in viremic HCV- (n = 15) or HIV-infected participants (n = 24) and uninfected controls (n = 10). Accelerated dosing HAV/HBV vaccine and tetanus booster were administered and antibody response was measured at 0, 1, 3, 8, and 24 weeks. Results: Pre-vaccine plasma IP10, IL-6, and sCD14 levels were elevated in both HCV and HIV-infected participants, while sCD163 was also elevated in HCV-infected participants. Pre-immunization tetanus antibody levels were lower in HIV-infected than in uninfected participants, while vaccine induced antibody responses were intact in HCV and HIV-infected participants. After HAV/HBV vaccination, HCV and HIV-infected participants had lower and less durable HAV and HBV antibody responses than uninfected controls. Among HCV-infected participants, pre-vaccine plasma IP10, IL-6, sCD14, and sCD163 levels inversely correlated with HAV, HBV and tetanus antibody responses after vaccine. Low HAV/HBV vaccine responses in HIV-infected participants prohibited assessment of immune correlates. Conclusions: During HCV and HIV infection markers of systemic inflammation reflect immune dysfunction as demonstrated by poor response to HAV/HBV neo-antigen vaccine.